2021
DOI: 10.1007/s43615-021-00112-2
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Innovative Alkali-Activated Binders for Soil Stabilisation in the Context of Engineering Sustainability and Circular Economy

Abstract: In the context of sustainability in the civil engineering industry, chemical ground improvement is becoming increasingly used, as a generally more sustainable alternative to replacing and landfilling unsuitable for construction ground. However, traditional soil stabilisers such as Portland cement or lime are not environmentally impact-free; international research effort is thus focusing on the development of innovative cementing agents. This paper presents results from a feasibility study on the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Since the introduction of the use of geopolymers as a cementitious binder to the engineering research community by Davidovits [72] and Duxson et al [73], the use of geopolymers for soil stabilisation purposes has also gained attention in recent years. The emergence of geopolymer applications to enhance the engineering properties of weak soils has proven its benefits to the geotechnical research community [74][75][76]. Abdullah [77] summarised the engineering benefits of using geopolymers to remediate the inherent weaknesses in problematic soils: (1) enhanced soil structure due to the synthesis of cementitious gels created in the soil voids; (2) increased strength of the soil matrix as the presence of geopolymer material improves the shear stress resistance of the stabilised soil.…”
Section: Geopolymersmentioning
confidence: 99%
“…Since the introduction of the use of geopolymers as a cementitious binder to the engineering research community by Davidovits [72] and Duxson et al [73], the use of geopolymers for soil stabilisation purposes has also gained attention in recent years. The emergence of geopolymer applications to enhance the engineering properties of weak soils has proven its benefits to the geotechnical research community [74][75][76]. Abdullah [77] summarised the engineering benefits of using geopolymers to remediate the inherent weaknesses in problematic soils: (1) enhanced soil structure due to the synthesis of cementitious gels created in the soil voids; (2) increased strength of the soil matrix as the presence of geopolymer material improves the shear stress resistance of the stabilised soil.…”
Section: Geopolymersmentioning
confidence: 99%
“…Traditional methods of chemical ground improvement include the addition of small percentages of Portland cement (Yoobanpot et al 2017 ) or lime (Ghorbani et al 2019 ; Kichou et al 2022 ; Zhang et al 2015a , b ) and also fly ash (Abdullah et al 2020 ; Deepak et al 2021 ). Recent options include more innovative cements such as alkali-activated cements/geopolymers (Ghadir and Ranjbar 2018 , Mavroulidou et al 2022 , 2023 ) or biocements, produced by the metabolic actions of microorganisms through various processes, including ureolysis (Omoregie et al 2021 ; Phillips et al 2013 ), photosynthesis (Irfan et al 2019 ), denitrification (Jain et al 2021 ; O’Donnell et al 2017 ), and methane oxidation (Ganendra et al 2014 ). This paper proposes instead the carbonic anhydrase metabolic pathway, as an innovative eco-friendly and sustainable soil stabilisation method, which can consume captured waste CO 2 or CO 2 from the atmosphere to precipitate CaCO 3 which binds together (biocements) soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the addition of various stabilizing agents improved the workability of soils [9][10][11][12][13]. For instance, adding cement improves the strength and bearing capacities of soils [14], while adding lime contributes to gain in strength in tested soil specimens [15].…”
Section: Introductionmentioning
confidence: 99%